THE EFFECT OF FINGER HOLD RELAXATION ON POST OPERATING PAIN IN PATIENTS AT RSUD DR. RASIDIN PADANG - Fridalni, Nova -; Yanti, Etri (STIKES Syedza Saintika Padang, 2023)
Everyone can experience pain to different degrees. Causes of pain include the result of trauma or surgery. Pain after surgery usually makes the patient feel very sick. The average patient feels severe pain in the first 2 hours postoperatively. The finger grip is very simple technique. This technique will produce impulses that are sent through non-nociceptor afferent nerve fibers which result in the